Implementasi Model Contextual Teaching and Learning Dalam Meningkatkan Hasil Belajar Siswa Pada Mapel Fikih Di MIN 2 Kota Surabaya - Dewi Arlifah Cahyani; Ika Rahmawati; Nur Aini; Bachtiar Hariadi (LPPM STAI Ihyaul Ulum Gresik, 2023)
Learning with the CTL (Contextual Teaching and Learning) model is a holistic learning process. The aim is to help students understand teaching material and relate it to everyday life, both in personal and social and cultural contexts. So they are knowledgeable, have dynamic and flexible skills. To actively construct your own understanding of the subject matter. Students can learn well if teaching materials related to knowledge and learning activities are known and are around the students. Based on the results of these observations, it is very necessary to implement CTL (Contextual Teaching and Learning) to improve student learning outcomes in the subject of Jurisprudence in order to know the extent of success in student learning outcomes in the subject of Jurisprudence. It is hoped that the results of this development will be useful for testing the effectiveness of implementing CTL (Contextual Teaching and Learning) in improving student learning outcomes. Based on these initial observations, the author is encouraged to research and study further about the implementation of CTL (Contextual Teaching and Learning) in improving student learning outcomes. in Fiqh subjects at MIN 2 Surabaya City.